Life-limiting health conditions, treatment and subsequent mortality associated with differences in health service use in people with severe mental illness: an analysis of the Northern Ireland population using administrative data sources. - Rachel McCarter; Michael Rosato; Gerry Leavey (International Journal of Population Data Science, 2022)
Objectives To examine differences in hospital admissions for people with severe mental illness (SMI), physical health multimorbidity and mortality compared to the general hospital population without SMI.